Epidemiology, Technology, and Professional Perspectives on Diabetes in the United Arab Emirate: A Focused Review - Dahmani, Khaled M. Al.; Suliman, Mohamed; Hafidh, Khadija; Beshyah, Salem A. (Journal of Diabetes and Endocrine Practice, 2024)
Introduction The United Arab Emirates (UAE), among the rest of the Arab Gulf countries, exhibits a high prevalence of diabetes, primarily type 2 diabetes (T2D).Methods We aimed to provide an overview of the epidemiology, complications, and quality of care, including the use of technology in diabetes care. Also, we wished to explore the challenges of diabetes management and future directions in clinical practice and research. This is a focused review of the literature of selected relevant themes to serve the above objectives of the work.Results Several epidemiological studies have documented the increased prevalence of diabetes in the native population and expatriates. The vast majority focused on T2D. The prevalence of diabetes in the UAE is estimated at 12.3% for the 20 to 79 age group. Although the high prevalence was recognized and acknowledged as a national priority, several challenges exist in standardizing care across the population. There are gaps in research about the nationwide prevalence of all forms of diabetes. Some research studies have evaluated the role of technology in diabetes care, genetic predilection to complications, and particular aspects such as diabetes during pregnancy, neonatal diabetes, monogenic diabetes, and cardiovascular risk in diabetes. UAE recently became a focal point for health-related Ramadan fasting research, including diabetes.Conclusion Diabetes in the UAE considerably burdens the health care system. A concerted effort is needed to adopt more uniformity of diabetes care and research nationwide. This should address the use of unified methods to document the nationwide burden, explore possible differences in various epidemiological phenomena, access to health care, and impact on outcomes, and evaluation of the cost-effectiveness of different models of care.
Keywords: complications; diabetes; diabetes care; epidemiology; management; professionalism; United Arab Emirates